2003
DOI: 10.1207/s15327663jcp1303_09
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Materialism Among Youth

Abstract: As an emerging value, materialism helps explain the consumer behavior of youth. Using a national sample of 9to 14-year-olds, in this study we developed a Youth Materialism Scale. The findings suggest that more materialistic youth tend to shop more and save less. They are most interested in new products and most responsive to advertising and promotional efforts. Their parents view them as more expert with regard to products and they wield more purchase influence on their parents. Parents who are more materialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
338
1
45

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(416 citation statements)
references
References 19 publications
16
338
1
45
Order By: Relevance
“…Alguns pesquisadores encontraram, por exemplo, uma relação entre os níveis de materialismo das crianças e de seus pais (e.g., Carslon & Grossbart, 1988;Goldberg, Gorn, Peracchio, & Bammossy, 2003), o mesmo ocorrendo com os níveis de hedonismo (Knafo & Schwartz, 2009). É graças também à interação com os adultos que a criança aprende que há valores que dizem respeito às ações humanas intencionais , os quais são denominados valores morais.…”
Section: Sistemas De Valores Na Infância E Adolescênciaunclassified
“…Alguns pesquisadores encontraram, por exemplo, uma relação entre os níveis de materialismo das crianças e de seus pais (e.g., Carslon & Grossbart, 1988;Goldberg, Gorn, Peracchio, & Bammossy, 2003), o mesmo ocorrendo com os níveis de hedonismo (Knafo & Schwartz, 2009). É graças também à interação com os adultos que a criança aprende que há valores que dizem respeito às ações humanas intencionais , os quais são denominados valores morais.…”
Section: Sistemas De Valores Na Infância E Adolescênciaunclassified
“…Materialisme yang tinggi adalah sebab bagi berbagai persoalan psikologi, sosial, ekonomi, dan pendidikan, seperti: rendahnya well-being, ketidakbahagiaan dan ketidakpuasan hidup, dan tingginya stres dan depresi (Brouskeli & Loumakou, 2014;Dittmar & Kapur, 2011;Garðarsdóttir, Janković & Dittmar, 2008;Karabati & Cemalcilar, 2010;Konow & Earley, 2008;Tatzel, 2002;Tsang, Carpenter, Roberts, Frisch, & Carlisle, 2014); perilaku mengkonsumsi yang bermasalah, seperti compulsive dan excessive buying (Dittmar, 2005;Müller, et al, in press, 2011;Pham, Yap, & Dowling, 2011); sikap dan perilaku tidak prolingkungan (Hurst, Dittmar, Bond, & Kasser, 2013;Kilbourne & Picket, 2008); sikap negatif terhadap pernikahan dan memiliki anak (Li, Patel, Balliet, Tov, Scollon 2010); ketidaksukaan menabung dan sekolah pada anak, rendahnya motivasi belajar intrinsik, meningkatnya motivasi belajar ekstrinsik, dan rendahnya performa akademik (Goldberg Gorn, Peracchio, & Bamosy, 2003;Ku, Dittmar, & Banerjee, 2014).…”
Section: Studi Materialisme Awal: Konsekuensi Dan Antesedenunclassified
“…Studies of American adolescents conducted since 2000 have developed a 10-item 'Youth Materialism Scale' for 9Á14 year olds (Goldberg et al 2003) and an 18-item 'Consumer Involvement Scale' comprising a broad range of consumer attitudes, values and activities for 10Á13 year olds (Schor 2004). While these scales measure consumerism as a personality attribute and/or value, a more recent study of 8Á18 year olds measured the concept via the number of material possessions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of children and adolescents reporting on gender differences in consumerism describe higher levels among males (Churchill and Moschis 1979, Goldberg et al 2003, Flouri 2004, Kasser 2005, although one found no gender difference (Nairn et al 2007). Results in respect of age are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation